Penerapan Sistem Maintenance Berkala pada Mesin Premoulding Hidrolik Press di PT MK Prima Indonesia melalui Kegiatan Praktik Kerja Nyata - Ulul Ilmi; Eko Vibi Nurwansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The Field Work Practice (PKN) carried out at PT MK Prima Indonesia focused on the implementation of periodic maintenance practices for the premoulding hydraulic press machine as an effort to maintain machine performance and operational lifespan. The main activities included identifying critical components such as the hydraulic system, valves, pressure hoses, and oil filters; conducting direct observation of common disruptions; and performing daily maintenance checklists that covered pressure monitoring, operating temperature, leakage detection, machine cleanliness, and lubrication conditions. Comprehensive cleaning procedures, condition-based filter replacement, and functional testing were also conducted to ensure reliability and safety in the production process. The implementation methods involved participatory observation, interviews with technicians regarding common failure patterns, visual and functional inspections, as well as the use of structured checklists supported by inspection documentation. The results indicate a significant decrease in the frequency of disturbances caused by leaks and oil contamination, improved compliance with routine inspection procedures, and enhanced machine readiness during operations. The introduction of structured documentation and simple technical training further improved technicians’ ability to detect early signs of abnormalities in the hydraulic system. As a recommendation, the company is advised to strengthen the use of digital recording systems, adjust filter replacement intervals based on actual machine conditions, and implement regular training programs focusing on contamination control and predictive maintenance.